Novel cetacean morbillivirus in a rare Fraser’s dolphin (Lagenodelphis hosei) stranding from Maui, Hawai‘i - West, Kristi L.; Silva-Krott, Ilse; Landrau-Giovannetti, Nelmarie; Rotstein, Dave; Saliki, Jeremiah; Raverty, Stephen; Nielsen, Ole; Popov, Vsevolod L.; Davis, Nicole; Walker, William A.; Subramaniam, Kuttichantran; Waltzek, Thomas B. (Scientific reports, 2021)
Cetacean morbillivirus (CeMV) is a global threat to cetaceans. We report a novel morbillivirus from a Fraser’s dolphin ( Lagenodelphis hosei ) that stranded in Maui, Hawaii in 2018 that is dissimilar to the beaked whale morbillivirus previously identified from Hawaii and to other CeMV strains. Histopathological findings included intranuclear inclusions in bile duct epithelium, lymphoid depletion, rare syncytial cells and non-suppurative meningitis. Cerebellum and lung tissue homogenates were inoculated onto Vero.DogSLAMtag cells for virus isolation and cytopathic effects were observed, resulting in the formation of multinucleated giant cells (i.e., syncytia). Transmission electron microscopy of infected cell cultures also revealed syncytial cells with intracytoplasmic and intranuclear inclusions of viral nucleocapsids, consistent with the ultrastructure of a morbillivirus. Samples of the cerebellum, lung, liver, spleen and lymph nodes were positive for morbillivirus using a reverse transcription-polymerase chain reaction. The resulting 559 bp L gene sequence had the highest nucleotide identity (77.3%) to porpoise morbillivirus from Northern Ireland and the Netherlands. The resulting 248 bp P gene had the highest nucleotide identity to porpoise morbillivirus in Northern Ireland and the Netherlands and to a stranded Guiana dolphin ( Sotalia guianensis ) in Brazil (66.9%). As Fraser’s dolphins are a pelagic species that infrequently strand, a novel strain of CeMV may be circulating in the central Pacific that could have additional population impacts through transmission to other small island-associated cetacean species.